Religious and Secular Motives for some English Monastic Foundations - Mortimer, Richard (Studies in church history, 1978)
Hanc autem donationem feci eis pro salute memorati domini mei illustris Regis Henrici et pro salute anime mee et Berthe uxoris mee, et omnium antecessorum et successorum nostrorum. Thus briefly Rannulf de Glanville explains his foundation of Leiston abbey, and we have no reason to doubt his word. This motive is completely conventional and occurs in virtually every contemporary monastic foundation charter, which underlines its validity rather than detracting from it. Perhaps there is no need to look further; but Glanville’s is not the only voice to be heard on the foundation of Leiston abbey, and the founder does not answer all the questions we should like to ask. Did he perhaps have other motives? How did he go about choosing a religious order? To these questions we have to find our own answers. We can arrange facts in a suggestive series, and then ascribe more or less simple intentions which explain them. The shortcomings of such a method are obvious, though the results can be plausible and are often the only ones available. The unreliability of the answer is our penance for the temerity of the question.